1996
DOI: 10.1111/j.1476-5381.1996.tb15357.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of P2U‐ and P2Y‐purinoceptors to endothelium‐dependent vasodilatation in the golden hamster isolated mesenteric arterial bed

Abstract: 1 P2-purinoceptors were characterized pharmacologically in the constantly perfused isolated mesenteric arterial vascular bed of the golden hamster. Vasoconstrictor and vasodilator responses to the nucleotides ATP, ADP, 2 methylthio ATP (2MeSATP), a,,B-methylene ATP (a,f,-meATP) and uridine 5'-triphosphate (UTP) and a role for ATP in sympathetic constriction were examined. After removal of the endothelium, with the exception of adenosine, vasodilator responses to purines and to UTP were abolished; vasoconstrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…Striking evidence for species differences between rabbit and rat mesenteric arterial purinergic signaling was presented in later studies, with the observation that ATP relaxation of rat mesenteric arteries was elicited largely via the endothelium (Vuorinen et al, 1992). Similarly, hyperpolarizations to ATP in hamster mesenteric arteries were endothelium dependent (Thapaliya et al, 1999), as were relaxations to ATP, ADP, and UTP in the hamster mesenteric arterial bed (Ralevic and Burnstock, 1996b).…”
Section: Mesenteric Vesselsmentioning
confidence: 92%
See 1 more Smart Citation
“…Striking evidence for species differences between rabbit and rat mesenteric arterial purinergic signaling was presented in later studies, with the observation that ATP relaxation of rat mesenteric arteries was elicited largely via the endothelium (Vuorinen et al, 1992). Similarly, hyperpolarizations to ATP in hamster mesenteric arteries were endothelium dependent (Thapaliya et al, 1999), as were relaxations to ATP, ADP, and UTP in the hamster mesenteric arterial bed (Ralevic and Burnstock, 1996b).…”
Section: Mesenteric Vesselsmentioning
confidence: 92%
“…Smooth muscle P2X receptors mediating contractile responses to ATP have been described in mesenteric arterial beds of both the rat Burnstock, 1988, 1991) and golden hamster (Ralevic and Burnstock, 1996b). Contractile responses were also evoked by a,b-meATP, which blocked responses to purine nucleotides, indicating likely actions at P2X 1 receptors (Ralevic and Burnstock, 1988, 1996b.…”
Section: Mesenteric Vesselsmentioning
confidence: 96%
“…On the contrary, in the hamster mesenteric arterial bed, prejunctional adenosine A 1 , but not P2, receptors modulate sympathetic neurotransmission [136]. The purinergic component of sympathetic neurotransmission does not contribute significantly to sympathetic contractile responses of this vascular bed [136,139]. It was suggested that inhibitory P2 receptors are expressed selectively on sympathetic nerves utilizing ATP as a cotransmitter, in accordance with the view that prejunctional P2 receptors on sympathetic nerve terminals are release-modulating autoreceptors [178,183].…”
Section: Effects Mediated By P2x and P2y Receptors In The Splanchnic mentioning
confidence: 86%
“…ATP may also induce vasorelaxation depending on the experimental conditions (level of pre-tone) and relative expression of relevant vasocontractile and vasorelaxant receptors [24,25]. In porcine pancreatic arteries, ATP induced a biphasic response consisting of a contraction followed by a relaxation (Fig.…”
Section: Discussionmentioning
confidence: 99%